2015
DOI: 10.1186/s12968-015-0123-3
|View full text |Cite
|
Sign up to set email alerts
|

Age- and gender-related normal left ventricular deformation assessed by cardiovascular magnetic resonance feature tracking

Abstract: BackgroundAssessment of left (LV) ventricular function is one of the most important tasks of cardiovascular magnetic resonance (CMR). Impairment of LV deformation is a strong predictor of cardiovascular outcome in various cardiac diseases like ischemic heart disease or cardiomyopathies. The aim of the study was to provide reference values for myocardial deformation derived from the CMR feature tracking imaging (FTI) algorithm in a reference population of healthy volunteers.MethodsFTI was applied to standard sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
143
4
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(192 citation statements)
references
References 22 publications
31
143
4
5
Order By: Relevance
“…The authors found higher strain values in women than in men and a decrease of peak left and right atrial strain with age, findings generally in line with the literature, 8,9 and new for the right atrium. Time-to-peak strain measurements from all chambers are also reported.…”
Section: See Article By Addetia Et Alsupporting
confidence: 79%
See 1 more Smart Citation
“…The authors found higher strain values in women than in men and a decrease of peak left and right atrial strain with age, findings generally in line with the literature, 8,9 and new for the right atrium. Time-to-peak strain measurements from all chambers are also reported.…”
Section: See Article By Addetia Et Alsupporting
confidence: 79%
“…From Figure 1 of Addetia et al (the only one with an electrocardiographic tracing), it seems that LV and left atrial strain curves both start at zero at the end of the electrocardiographic QRS complex. However, physiologically, left atrial (LA) expansion in sinus rhythm starts at the onset or even before the QRS complex 5,7 (see Figure), and LV longitudinal shortening also starts during QRS.The authors found higher strain values in women than in men and a decrease of peak left and right atrial strain with age, findings generally in line with the literature, 8,9 and new for the right atrium. Time-to-peak strain measurements from all chambers are also reported.…”
supporting
confidence: 80%
“…Similar trend was observed in healthy human volunteers [17]. Coronary interventions were associated with acute LV dysfunction.…”
Section: Functionsupporting
confidence: 62%
“…Strain and strain rate were obtained using standard cine SSFP sequences with the settings noted above for the short axis stack and CMR feature-tracking (FT, '2D CPA MR' software, TomTec, Unterschleissheim, Germany), as previously described (15,16): Endocardial borders were contoured on mid-systolic frames.…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%